Children of the Revolution: Women's Liberation and Children's Success - Eric Maurin; Florentine Oliveira (Institute of Labor Economics (IZA), 2024)
In many countries, the Sixties marked a turning point in the history of women's emancipation. Using data with information on the birth order of large samples of individuals, we show that the first to be affected by this revolution were the first-born of the early 1960 s: they grew up much more often in "modern" families (two children max, working mother and significant likelihood of parental divorce) than children of higher birth orders born at the same time in other families. However, this change in family environment did not coincide with any decline in their educational or occupational achievement.
Keywords: J11; J12; J13; I24; 330; Sixties; family size; maternal employment; education